2020
DOI: 10.3390/su122410691
|View full text |Cite
|
Sign up to set email alerts
|

How Green FinTech Can Alleviate the Impact of Climate Change—The Case of Switzerland

Abstract: The financial services industry is currently undergoing a major transformation, with digitization and sustainability being the core drivers. While both concepts have been researched in recent years, their intersection, often conceived as “green FinTech,” remains under-determined. Therefore, this paper contributes to this important discussion about green FinTech by, first, synthesizing the relevant literature systematically. Second, it shows the results of an empirical, in-depth analysis of the Swiss FinTech la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(87 citation statements)
references
References 62 publications
3
59
0
2
Order By: Relevance
“…This suggests that Jordanians are more likely to increase their adoption of FinTech services if they see the value of such systems. These technologies and services may be valuable because they save time, effort, and money while decreasing product waste, chemicals, and resources [7,8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that Jordanians are more likely to increase their adoption of FinTech services if they see the value of such systems. These technologies and services may be valuable because they save time, effort, and money while decreasing product waste, chemicals, and resources [7,8].…”
Section: Discussionmentioning
confidence: 99%
“…Aside from the benefits it provides to users and businesses by making operations and transactions considerably easier, FinTech acts as a catalyst for the long-term development of developing economies. FinTech services can help limit environmental effects by increasing productivity, efficiency, and cost savings; reducing product waste, chemicals, and resources; and measuring, analyzing, and tracking progress [7,8]. Sustainability has evolved from a specialist business concern to a mainstream one.…”
Section: Introductionmentioning
confidence: 99%
“…Arner et al ( 2020 ) have proclaimed that Fintech functions as a facilitator for financial inclusion, which in turn aids in the achievement of sustainable development. Puschmann et al ( 2020 ) have argued that Fintech and green finance assist in achieving the clean energy that is also mandated in sustainable development goals. All these studies reveal that Fintech can act a facilitating role on achieving energy efficiency.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A study found that digital finance can effectively reduce energy consumption per unit of GDP in the real economy by promoting the development of technology-intensive manufacturing and other paths, and is a new engine for green development in China. Puschmann measured green total factor productivity (GTFP) using an SBM model that includes non-desired output and explored the relationship between digital finance and GTFP and the underlying mechanism [31]. Puschmann concluded that digital finance could improve GTFP through indirect mechanisms such as technological innovation and regional entrepreneurship.…”
Section: The Green Effect Of Financial Digitizationmentioning
confidence: 99%